Diagnosis and Management of Genetic Causes of Middle Aortic Syndrome in Children: A Comprehensive Literature Review - Lazea C; Al-Khzouz C; Sufana C; Miclea D; Asavoaie C; Filimon I; Fufezan O (Dove Medical Press, 2022)
Cecilia Lazea,1,2 Camelia Al-Khzouz,1,3 Crina Sufana,2 Diana Miclea,3,4 Carmen Asavoaie,5 Ioana Filimon,5 Otilia Fufezan5 1Department Mother and Child, University of Medicine and Pharmacy "Iuliu Hatieganu", Cluj-Napoca, Romania; 2Department of Pediatrics I, Emergency Pediatric Hospital, Cluj-Napoca, Romania; 3Department of Medical Genetics, Emergency Pediatric Hospital, Cluj-Napoca, Romania; 4Department of Molecular Sciences, University of Medicine and Pharmacy "Iuliu Hatieganu", Cluj-Napoca, Romania; 5Department of Radiology and Medical Imaging, Emergency Pediatric Hospital, Cluj-Napoca, RomaniaCorrespondence: Cecilia Lazea, Department Mother and Child, University of Medicine and Pharmacy "Iuliu Hatieganu", 68, Motilor Street, Cluj-Napoca, 400370, Romania, Tel +40 744353764, Email cecilialazea@umfcluj.ro; cicilazearo@yahoo.comAbstract: Middle aortic syndrome (MAS) is a rare vascular disease representing an important cause of severe hypertension in children. MAS is characterized by segmental or diffuse narrowing of the abdominal and/or distal descending aorta with involvement of the renal and visceral branches. Most cases of MAS are idiopathic, but MAS may occur in genetic and acquired disorders. The most common genetic causes of MAS are neurofibromatosis type I, Williams syndrome, Alagille syndrome, tuberous sclerosis and mucopolysaccharidosis. This review article discusses the pathophysiological aspects, distinctive associated features, and management of genetic forms of MAS in children.Keywords: middle aortic syndrome, hypertension, neurofibromatosis type 1, Williams syndrome, Alagille syndrome, tuberous sclerosis, mucopolysaccharidoses